Search of Extended Objects in the Southern Sky (SExOSS) using S-PLUS DR1: photometric characterization of extragalactic sources - Haack, Rodrigo (2021)
The SExOSS (Search of Extended Objects in the Southern Sky) project is planning to study alarge sample of extended sources in the southern sky. Using The Southern Photometric Local Universe Survey(S-PLUS) data taken in 12 filters (5 broad + 7 narrow bands), the first step will consist to analyze the photometricrelationships shown using the broandband magnitudes, and through a deeper characterization made from narrowband filters behaviour. Such a characterization could reveal the existence of new photometric relationshipsinvolving one or more of those narrow band magnitudes available in this survey. In the present work, the firstresults obtained are shown, on a sample of extended sources included in the first data release (DR1) of S-PLUS.This first release corresponds to the Stripe-82 sky area previously observed by the Sloan Digital Sky Survey (SDSS).For our analysis, we considered a subsample of objects that had spectra in the SDSS to be able to perform aspectroscopic classification of their internal activity (galaxies with/without star formation, active nuclei, etc.) andthen searching for links between the properties shown in the narrow band photometry. The S-PLUS DR1 hasmore than 3 × 105sources, of which about 3 × 104 have been found to be extended and matched in the SDSS. Wepresent here the results obtained on a subsample selected by considering threshold values for the signtal-to-noiselevel in both the SDSS spectra and the magnitude value in the DR1 database, on which a blind classification ofinternal activity was carried out.